Analisis pengaruh CAR, ROA, NPL, BOPO dan DPK terhadap penyaluran kredit UMKM di Indonesia (Studi pada bank umum yang terdaftar di BEI periode 2010-2012) - Widiyanti '; Muchtar Mariso; Sjahruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is to aimed to analize the factors measured by CAR (Capital Adequacy Ratio), ROA (Return On Assets), NPL (Non performing Loan), BOPO (operating expense to operating revenue ratio) and DPK (third party fund) that influence SMEs loan disbursement in Indonesian commercial banks that listed in Indonesia Stock Exchange (IDX) from 2010 to 2012. There are 32 banking companies listed in IDX for period 2010-2012 which have been selected. The analyze technique used to test the hypothesis in this study is multiple regression. The result concluded that simultaneously CAR, ROA, NPL, BOPO and DPK influence the SMEs lending. Partially, DPK has positive significance influence to SMEs lending; meanwhile, CAR, ROA, NPL and BOPO have no significance influence to SMEs lending.Keywords : Lending, SMEs, CAR (Capital Adequacy Ratio), ROA (Retun On Asset), NPL (Non Performing Loan), BOPO (operating expense to operating revenue ratio), DPK (third party fund)